2020
DOI: 10.1002/celc.202000026
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Oxygen Functional Groups in Carbon Nanotubes‐Supported Ag Catalysts for Electrochemical Conversion of CO2 to CO

Abstract: Carbon nanotubes (CNTs)-supported metal-based catalysts applied in the electrochemical reduction of CO 2 (CO 2 ER) have attracted extensive research recently. Nevertheless, insight into the roles of surface oxygen functional groups in these catalysts on CO 2 ER is still deficient. Herein, three catalysts were reasonably fabricated by chemically loading Ag nanoparticles (NPs) on the oxygenic CNTs (CNTÀ COOH, CNTÀ OH and CNTÀ CO) with precise tuning oxygen functional groups, and then used to explore the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…The measured Tafel slope for AgNPs@PAM is 133 mV dec −1 , which is comparable to the 118 mV dec −1 expected for rate‐limiting single‐electron transfer from the adsorbed *CO 2 to form the surface‐adsorbed *CO 2 .− [45] . However, the smaller Tafel slope for AgNPs@PAM relative to our previously reported values for Ag NPs with sizes of approximately 5 nm [46] also suggests that the introduction of PAM may contribute to the enhancement of the intrinsic activity of Ag NPs. In addition, the electrochemical stability of AgNPs@PAM was measured at −0.79 V by prolonging the electrolysis.…”
Section: Resultssupporting
confidence: 68%
“…The measured Tafel slope for AgNPs@PAM is 133 mV dec −1 , which is comparable to the 118 mV dec −1 expected for rate‐limiting single‐electron transfer from the adsorbed *CO 2 to form the surface‐adsorbed *CO 2 .− [45] . However, the smaller Tafel slope for AgNPs@PAM relative to our previously reported values for Ag NPs with sizes of approximately 5 nm [46] also suggests that the introduction of PAM may contribute to the enhancement of the intrinsic activity of Ag NPs. In addition, the electrochemical stability of AgNPs@PAM was measured at −0.79 V by prolonging the electrolysis.…”
Section: Resultssupporting
confidence: 68%
“…Due to its unique properties [3,4], carbon nanotubes and nanofibers are one of the most promising classes of NMs, which currently are in the growth phase of large-scale bulk production [5]. Carbon nanotubes were successfully used in electronics [6], catalysis [7,8], environmental purification [9,10], biomedicine [11,12], and other fields. Carbon nanofibers have an application in energy storage [13,14], electronics [15], catalysis [16,17], biosensing [18], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray diffraction (XRD) patterns indicated that the deposited Sn nanoparticles existed as oxide forms (SnO and SnO 2 ) (cf., Figure S4a in the Supporting Information), and the characteristic Raman peaks of CNTs at 1358 cm –1 (D band) and 1582 cm –1 (G band) in Figure S4b in the Supporting Information verified that the original property of CNT was maintained in the Sn-CHF . The X-ray photoelectron spectroscopy (XPS) for deconvolution of C 1s and O 1s spectra (cf., Figure S5 in the Supporting Information) indicated identical functional groups for the Sn-CHF with different Sn loadings. The Sn 3d 5/2 and 3d 3/2 spectra of the Sn-CHF from the high-resolution XPS were indicated at 487.5 and 496.5 eV, respectively (cf., Figures h and S5 in the Supporting Information) and could be deconvoluted into SnO x and Sn. , We note that metal oxides are thermodynamically unstable, and SnO x should be reduced to metallic states under neutral to acidic CO 2 reduction conditions, while under alkaline conditions, oxide phases could coexist . The Brunauer–Emmett–Teller (BET) analysis of the Sn-CHF at different loadings showed mesopores with an average pore size from 13.4 to 19.58 nm, and the calculated specific surface area was ranged from 60.83 to 86.7 m 2 /g (Table S1 of the Supporting Information).…”
mentioning
confidence: 99%